HUBUNGAN KEMAMPUAN GURU DALAM MENGELOLA KELAS DENGAN PROSES BELAJAR MENGAJAR PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) DI MTS NEGERI BATURAJA - Azhar Azhar (STAI Bumi Silampari, 2019)
The quality of life of the nation is largely determined by educational factors. In carrying out this research, the author uses quantitative research methods. quantitative approach, descriptive analysis through library research and field research. The results teacher's ability to manage classes in MTs Negeri Baturaja is in the moderate category 45.62%. means to be quite good because it is supported by the sincerity of teachers in providing religious understanding and guidance to these students. The results of the next study can be concluded that the teaching and learning process in the subjects of Islamic Culture History (SKI) in Baturaja State MTs is in the moderate category 59.65%. that the teaching and learning process in Islamic Culture History (SKI) subjects at Baturaja State MTs seems to be quite good because it is supported by positive student habits and activities.